EEC‐ and ADULT‐Associated TP63 Mutations Exhibit Functional Heterogeneity Toward P63 Responsive Sequences. Issue 6 (2nd April 2013) - Monti, Paola; Russo, Debora; Bocciardi, Renata; Foggetti, Giorgia; Menichini, Paola; Divizia, Maria T.; Lerone, Margherita; Graziano, Claudio; Wischmeijer, Anita; Viadiu, Hector; Ravazzolo, Roberto; Inga, Alberto; et al.
<x xml:space="preserve">Abstract</x> Germline TP63 mutations are responsible for a group of human ectodermal dysplasia syndromes. Different TP63 alleles identified in ADULT and EEC patients were functionally characterized in yeast, studied in a mammalian cell line and modeled based on the crystal structure of the P63 DNA‐binding domain. Interestingly, the mutants associated with the ADULT phenotype were characterized by a severe defect in transactivation on DN‐P63α‐specific response elements derived from genes closely related to the clinical manifestations of the TP63‐associated syndromes, namely PERP and COL18A1. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>